Proceedings of the International Workshop on Rock Mass Classification in Underground Mining - Mark, Christopher; Pakalnis, Rimas Thomas, 1956-; Tuchman, Robert J. (U.S. Dept. of Health and Human Services, Centers for Disease Control and Prevention, National Institute for Occupational Safety and Health, Pittsburgh Research Laboratory, 2007)
"Rock mass classification is widely used throughout the underground mining industry--in both coal and hardrock mines. It is used in all stages of the mining process, from site characterization to production operations. The goal of the International Workshop on Rock Mass Classification in Underground Mining was to provide a forum for leading practitioners of rock mass classification to come together and share their methods and experiences with the technique. The workshop was held in Vancouver, British Columbia, Canada, on May 31, 2007"--Page 1
Title from tltle screen (viewed on March 25, 2008).
"May 2007."
Keywords: Ground control (Mining) -- United States -- Congresses.; Mining geology -- United States -- Congresses.; Rocks -- United States -- Classification -- Congresses.; Rocks -- United States -- Testing -- Congresses.; Mine roof control -- United States -- Equipment and supplies -- Congresses.; Geology.; Ground control (Mining) -- Congresses.; elektronické knihy; electronic books